Computer research on the accuracy of probe method for measuring the electrical contact resistance “metal – thermoelectric material” - Lysko, V.V.; Anatychuk , L.I.; Strusovskyi, K.I. (Journal of Thermoelectricity, 2023)
Physical and computer models have been created to study possible errors in measuring “metal-thermoelectric material” electrical contact resistance by probe method. By means of computer simulation, the distributions of electric potential and temperature in the studied physical model were obtained for different sample geometries, current through the sample, and contact electrical resistance. It was found that deviations from isothermal conditions in the sample, caused by the influence of the Joule and Peltier effects, can lead to very significant (over 100%) errors in measurements. The possibilities of minimizing these errors by thermostating one side of the sample are considered. Bibl. 12, Figs. 14.